2007
DOI: 10.1002/ejoc.200700388
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Reactivity of Chalcogenyl Phosphonates and Phosphane Oxides

Abstract: The preparation of new bis[(diphenylphosphinoyl)methyl] sulfides, selenides, and tellurides is described by the reaction of (diphenylphosphinoyl)methyl p-toluenesulfonate with sodium chalcogenides. The title compounds are subjected to Horner-Wittig-type reactions with aldehydes and ketones to give symmetrical divinylic sulfides, selenides, and tellurides

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 66 publications
2
13
0
Order By: Relevance
“…The crude product was recrystallized (CH 2 Cl 2 /Et 2 O, 1:9) to give pure diphenyl{[(p-tolylsulfonyl)oxy]methyl}phosphane oxide as a white solid (3.93 g, 71 %). [36] The analytical data for this compound match that previously reported. [36] To a solution of the diphenyl{[(p-tolylsulfonyl)oxy]methyl}phosphane oxide (3.86 g, 10.0 mmol) in acetone (200 mL) was added sodium iodide (5.99 g, 40.0 mmol).…”
Section: Preparation Of Diethyl (1-iodopent-4-enyl)phosphonate (2d)supporting
confidence: 70%
See 1 more Smart Citation
“…The crude product was recrystallized (CH 2 Cl 2 /Et 2 O, 1:9) to give pure diphenyl{[(p-tolylsulfonyl)oxy]methyl}phosphane oxide as a white solid (3.93 g, 71 %). [36] The analytical data for this compound match that previously reported. [36] To a solution of the diphenyl{[(p-tolylsulfonyl)oxy]methyl}phosphane oxide (3.86 g, 10.0 mmol) in acetone (200 mL) was added sodium iodide (5.99 g, 40.0 mmol).…”
Section: Preparation Of Diethyl (1-iodopent-4-enyl)phosphonate (2d)supporting
confidence: 70%
“…[36] The analytical data for this compound match that previously reported. [36] To a solution of the diphenyl{[(p-tolylsulfonyl)oxy]methyl}phosphane oxide (3.86 g, 10.0 mmol) in acetone (200 mL) was added sodium iodide (5.99 g, 40.0 mmol). The mixture was heated to 75°C for 24 h, quenched with sodium thiosulfate (saturated aqueous, 100 mL), and extracted with ethyl acetate (3 ϫ 100 mL).…”
Section: Preparation Of Diethyl (1-iodopent-4-enyl)phosphonate (2d)supporting
confidence: 70%
“…[31][32][33][34][35][36][37][38] In this regard, our continuous interests in the synthesis of organochalcogen compounds prompted us to access symmetrical and unsymmetrical vinyl suldes by a straightforward approach, using a Wittig-Horner reaction, as precursors of products carrying a higher oxidation state on sulfur. 39,40 In this sense, photoactive divinyl suldes and sulfones have been obtained. 31,41 However, there is a lack of information on the rationalization of comparative electronic effects exerted by organosuldes, sulfoxides and sulfones on excited and ground states of pushpull p-conjugated structures.…”
Section: Introductionmentioning
confidence: 99%
“…38,[61][62][63][64] Analysis of the 1 H NMR and 13 C NMR spectra showed that all alkene compounds presented data in full agreement with their assigned structures. The stereochemistry of the obtained alkenes was easily established.…”
Section: Resultsmentioning
confidence: 97%